Moving Beyond the Question of Education or Exploitation: The Dynamic Experiences of Black Male Student-Athletes - Jonathan Howe; Marc Johnston-Guerrero (University of Kansas Libraries, 2021)
When discussing the Black male student-athlete, dominant perspectives argue that they are being educated while another perspective argues that this population is being exploited. This article moves beyond the question of whether Black male student-athletes are being educated or exploited as we argue that both can happen. Utilizing Critical Race Theory, we highlight dominant perspectives about Black male student-athletes as well as offer an analysis of their experiences. The article provides the presentation of a fictive counterstory that portrays the notion that this population can experience education and exploitation. We conclude by offering a discussion about approaches that institutions and athletic departments can take to better serve Black male student-athletes, including adopting the Excellence Beyond Athletics approach (Cooper, 2016).